Cytotoxicity of non-vital dental bleaching agents in human gingival fibroblasts - Fernandes, Aletéia Massula; Marques, Marcia Martins; Camargo, Samira Esteves Afonso; Cardoso, Paula Elaine; Camargo, Carlos Henrique Ribeiro; Valera, Marcia Carneiro (Brazilian Dental Science, 2013)
Purpose: The aim of this study was to compare several non-vital dental bleaching agents for their in vitro cytotoxicity to human gingival fibroblasts primary cell line. Methods: The cells were cultivated in DMEM and were seed in plates of 96 wells; then, it was exposed to the conditioned medium according to the experimental groups (n=12): G1- SP (sodium perborate) + distilled water; G2- SP + 20% CP (carbamide peroxide); G3- 20% CP; G4- SP + 35% HP (hydrogen peroxide); G5- 35% HP. In the control group (n=12), corresponded to the curve of cell growth and viability, the cells did not receive any treatment. Cell viability was measured photometrically using a MTT assay after a 24h and 48h of exposure period. Data were submitted to ANOVA and Tukey’s tests. Results: All the experimental groups presented high cytotoxicity statically in comparison to the control group. The rank of the most to the least toxic material after 24 hours was: SP + DW > 35% PH > PS + 20% PC > PS + 35% PH > 20% PC; and after 48 hours was: SP + DW > PS + 20% PC > 35% PH > PS + 35% PH > 20% PC. All the bleaching agents had presented cytotoxicity effects, reducing significantly the cell viability, however, in the conditions that the study was conducted the association of sodium perborate with distilled water was the most toxic bleaching agent.